Phononic Crystals 2016
DOI: 10.1007/978-1-4614-9393-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Surface Acoustic Waves in Phononic Crystals

Abstract: Over the past two decades, propagation of acoustic waves in periodic structures comprised of multi-components has received much attention because of renewed physical properties and potential applications in a variety of fields, such as noise and vibration isolation, frequency filters in wireless communication, super lens design, etc. These composite materials, called phononic crystals (PCs) [1,2], give rise to forbidden gaps for acoustic waves which are analogous to the band gaps for electromagnetic waves in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The values of the two curves are normalized by the spectral maximum amplitude of the substrate. In the lower curve of Figure 5(a), the phononic crystal is seen to attenuate |uz| at all frequencies, as might be expected with the introduction of scattering centres (Wu, et al, 2016) along the path of the SAW. However, the transmitted wave through the phononic crystal is considerably less between 400 MHz and 450 MHz.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The values of the two curves are normalized by the spectral maximum amplitude of the substrate. In the lower curve of Figure 5(a), the phononic crystal is seen to attenuate |uz| at all frequencies, as might be expected with the introduction of scattering centres (Wu, et al, 2016) along the path of the SAW. However, the transmitted wave through the phononic crystal is considerably less between 400 MHz and 450 MHz.…”
Section: Resultssupporting
confidence: 60%
“…While these wet-etched holes do provide a platform to demonstrate waveguiding behaviour along the GaAs surface, the larger than desired attenuation is mimicked in the simulations, which have estimated decay constant of approximately 1 dB/a. The leakage of acoustic power into the phononic crystal and bulk may be caused by the Pseudo-SAW behaviour of GaAs along the [110] direction (Webster & Carr, 1985), radiating into the substrate bulk (Wu, et al, 2016), or the coupling of multiple modes present in the bandgap (Pennec, et al, 2010). Further analysis into the origins of the decay mechanism will not be studied here.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the spatial periodicity of the PC, see Figure 1, it results (Laude and Khelif, 2016;Wu et al, 2016) r(rÞ = r(r + a);…”
Section: Modeling Pc Band Structurementioning
confidence: 99%
“…Both experimental (Malfanti et al, 2011;Yankin et al, 2014) and numerical (Li et al, 2012) studies are today available. The computational modeling is approached through finite difference, finite element (FE), or plane wave expansion (PWE) methods (see Assouar and Oudich, 2011;Li et al, 2012;Wu et al, 2016). FE analysis and experimental study of SAW propagation through twodimensional pillar-based surface PC is reported for example in Yankin et al (2014) and Guo et al (2016), while the P-Matrix method is used in Tian et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Phononic crystal (PnC) structures for controlling surface acoustic wave (SAW) propagation have been studied as an alternative to traditional metal gratings for applications requiring SAW guiding, reflecting and electronic device integration [1]. One significant design challenge of PnCs for SAW devices is the bulk mode conversion losses from leaky SAWs [2].…”
Section: Introductionmentioning
confidence: 99%